The Fragile X-Associated Tremor Ataxia Syndrome (FXTAS) - Tassone, Flora; Berry-Kravis, Elizabeth M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
In The Fragile X-Associated Tremor Ataxia Syndrome (FXTAS), the editors present information on all aspects of FXTAS, including clinical features and current supportive management, radiological, psychological, and pathological findings, genotype-phenotype relationships, animal models and basic molecular mechanisms. Genetic counseling issues are also discussed. The book should serve as a resource for professionals in all fields regarding diagnosis, management, and counseling of patients with FXTAS and their families, as well as presenting the molecular basis for disease that may lead to the identification of new markers to predict disease risk and eventually lead to target treatments.
Clinical Neurological Phenotype of FXTAS -- The Epidemiology of FXTAS -- FXTAS: Neuropsychological/Neuropsychiatric Phenotypes -- Radiological Findings in FXTAS -- The Pathology of FXTAS -- The Molecular Biology of FXTAS -- Genotype/Phenotype Relationships in FXTAS -- Animal Models for FXTAS -- Treatment and Management of FXTAS -- Genetic Counseling for FXTAS and FMR1-Associated Disorders.
Keywords: Medicine; Human genetics; Molecular biology; Neurosciences; Biomedicine; Human Genetics; Molecular Medicine; Neurosciences; Electronic books